2015
DOI: 10.1371/journal.pone.0134269
|View full text |Cite
|
Sign up to set email alerts
|

Collective Intelligence Meets Medical Decision-Making: The Collective Outperforms the Best Radiologist

Abstract: While collective intelligence (CI) is a powerful approach to increase decision accuracy, few attempts have been made to unlock its potential in medical decision-making. Here we investigated the performance of three well-known collective intelligence rules (“majority”, “quorum”, and “weighted quorum”) when applied to mammography screening. For any particular mammogram, these rules aggregate the independent assessments of multiple radiologists into a single decision (recall the patient for additional workup or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
112
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 40 publications
6
112
0
3
Order By: Relevance
“…Diagnostic accuracy was consistently greater with increasing group size, similar to findings of earlier literature on medical student teams 11,16 and combinations of user opinions for image interpretation. 8,9,10 These findings held across a broad range of specifications for creating a collective differential. These findings suggest that using the concept of collective intelligence to pool many physicians’ diagnoses could be a scalable approach to improve diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Diagnostic accuracy was consistently greater with increasing group size, similar to findings of earlier literature on medical student teams 11,16 and combinations of user opinions for image interpretation. 8,9,10 These findings held across a broad range of specifications for creating a collective differential. These findings suggest that using the concept of collective intelligence to pool many physicians’ diagnoses could be a scalable approach to improve diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 71%
“…5 The ability of collective intelligence—groups of individuals acting independently or collectively—to outperform individuals acting alone has gained prominence in politics, business, and economics, with studies identifying conditions in which collective intelligence appears beneficial. 8,9,10,11,12,13,14,15 Collective intelligence facilitated by software is particularly well suited for medicine because it may offer superior performance with little coordination.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its potential to boost accuracy in a wide range of contexts, including lie detection, political forecasting, investment decisions, and medical decision making (8)(9)(10)(11)(12)(13)(14), little is known about the conditions that underlie the emergence of collective intelligence in real-world domains. Which features of decision makers and decision contexts favor the emergence of collective intelligence?…”
mentioning
confidence: 99%
“…Reducing the frequency of diagnostic errors is thus a major step toward improving health care (24,25). Previous research on collective intelligence in medical diagnostics has yielded conflicting results: Some studies have found that group decision making boosts diagnostic accuracy (9,12,26,27), whereas others have found null or even detrimental effects (28,29).…”
mentioning
confidence: 99%
“…In principle, the larger the group, the higher the prediction accuracy (see for review Ponsonby & Mattingly, 2015), which led to the development of several crowdsourcing initiatives for diagnostic purposes (for instance, Candido dos Reis et al , 2015; Lau et al , 2016). However, when expert people are involved, even small groups can outperform the best among them, at least when a yes/no answer to well-defined diagnostic questions is requested based on radiographic/ histological images, ( Kurvers et al , 2016; Sonabend et al , 2017; Wolf et al , 2015). Studies with medical students show that working in pairs ameliorates diagnostic ability, with further improvements when group size increases ( Hautz et al , 2015; Kämmer et al , 2017), in line with the core idea of Collective intelligence.…”
Section: Introductionmentioning
confidence: 99%